Recommendation to include hydroxyethyl (meth)acrylate in the British baseline patch test series. (21st April 2019) - Rolls, S.; Chowdhury, M.M.; Cooper, S.; Cousen, P.; Flynn, A.M.; Ghaffar, S.A.; Green, C.M.; Haworth, A.; Holden, C.; Johnston, G.A.; Naidoo, K.; Orton, D.I.; et al.
Summary: Background: (Meth)acrylates are potent sensitizers and a common cause of allergic contact dermatitis (ACD). The frequency of (meth)acrylate ACD has increased with soaring demand for acrylic nails. A preliminary audit has suggested a significant rate of positive patch tests to (meth)acrylates using aimed testing in patients providing a clear history of exposure. To date, (meth)acrylates have not been routinely tested in the baseline patch test series in the U.K. and Europe. Objectives: To determine whether inclusion of 2‐hydroxyethyl methacrylate (2‐HEMA) 2% in petrolatum (pet.) in the baseline series detects cases of treatable (meth)acrylate ACD. Methods: During 2016–2017, 15 U.K. dermatology centres included 2‐HEMA in the extended baseline patch test series. Patients with a history of (meth)acrylate exposure, or who tested positive to 2‐HEMA, were selectively tested with a short series of eight (meth)acrylate allergens. Results: In total 5920 patients were consecutively patch tested with the baseline series, of whom 669 were also tested with the (meth)acrylate series. Overall, 102 of 5920 (1·7%) tested positive to 2‐HEMA and 140 (2·4%) to at least one (meth)acrylate. Had 2‐HEMA been excluded from the baseline series, (meth)acrylate allergy would have been missed in 36 of 5920 (0·6% of all patients). The top (meth)acrylates eliciting a positive reaction were 2‐HEMA ( n = 102, 1·7%), 2‐hydroxypropyl methacrylate ( n = 61, 1·0%) and 2‐hydroxyethyl acrylate ( n = 57, 1·0%). Conclusions: We recommend that 2‐HEMA 2% pet. be added to the British baseline patch test series. We also suggest a standardized short (meth)acrylate series, which is likely to detect most cases of (meth)acrylate allergy. Abstract : What's already known about this topic? A significant rate of sensitization to (meth)acrylates has been demonstrated worldwide. Increasing demand for acrylic nail fashion is putting consumers and nail technicians at risk of sensitization to (meth)acrylates. What does this study add? Inclusion of 2‐hydroxyethyl methacrylate (2‐HEMA) 2% in petrolatum (pet.) in the baseline series detects treatable (meth)acrylate allergic contact dermatitis (ACD). Identifying (meth)acrylate ACD is important as it can have adverse health consequences for patients who require composite fillings, surgical glue and bone cement, all of which contain (meth)acrylates. We recommend that 2‐HEMA 2% pet. be added to the British baseline patch test series, and to baseline series used in other countries. Linked Comment: Goncalo. Br J Dermatol 2019; 181 :663–664 . Plain language summary available online Respond to this article